Role of Vitamin D Deficiency on The Onset and Prognosis of Bell’s Palsy - Ocak, Emre; Sefa Uyar, Muhammed; Kocaoz, Deniz; Mirici, Emre; Acar, Aydin (ENT Updates, 2020)
Objective: To investigate the role of vitamin D on the etiology and the prognosis of Bell’s Palsy (BP). Methods: A prospective controlled clinical study was conducted on patients diagnosed as BP and healthy volunteers as control group. Vitamin D levels were measured in all subjects. In a homogenous group, effects of vitamin D on the etiology and prognosis were evaluated according to House-Brackmann (HB) grades of participants. Results: Vitamin D levels were similar in the BP and control groups. In BP group, patients with advanced HB grades had lower vitamin D levels. Moreover poorer outcomes (p=0.01) were achieved in patients who had <10ng/ml vi-tamin D, regardless the initial HB grade. Conclusion: Our results demonstrated a possible role of vitamin D levels on the prognosis of BP. Lower vitamin D levels may have a negative effect on recovery particularly in patients with advanced grades